Review of civilian experience in conflict situation - Yero, Aliyu; Othman, Jamilah; Talib, Ahmad Tarmizi; Ahmad, Shamsuddin; D' Silva, Jeffrey Lawrence (Canadian Center of Science and Education, 2014)
There is a growing concern among scholars on how the battlefield of conflict/wars have shifted to civilian populated areas causing huge pain and loss, previous studies have shown that civilians today have become entangled in a precarious situation where conflicts rage forcing them to either take charge of their fate or risk living in continuous fear of being used as scape-goats by either of the parties in conflict. This paper strife’s to bring to fore some of the challenges faced by civilians in conflict. Also, by reflecting on previous studies, room will be created for a prompt analysis of what civilians go through in the event of an impending conflict. Using existent literature, previous studies and reports from international organizations and actors in the field of conflict management, the paper highlight the nature, impact and experiences related to conflict and how these processes undermine the realization of basic human needs for survival among civilians. Borrowing from the Human Needs theory, the paper concludes that the realization of human potentials will not be attainable unless the need for security and safety is guaranteed. Failure to protect civilians in need of protection will ultimately put the faith of the people in their hands and thus promote the proliferation of light arms which has the potential for misuse and further endangering the civilian population.